Therapieresistente und ‑refraktäre Hypertonie - Düsing, Rainer (DMW - Deutsche Medizinische Wochenschrift, 2020)
Hypertension is defined as resistant to treatment when treatment fails to lower office systolic and diastolic blood pressure values to < 140/90 mmHg. The treatment strategy should include lifestyle measures and appropriate doses of three or more drugs acting by different mechanisms including a diuretic. An updated definition of treatment resistance includes all patients with ≥ 4 antihypertensive agents of different classes irrespective of their on-treatment blood pressure. The term “refractory” hypertension has been suggested for patients with uncontrolled blood pressure on ≥ 5 antihypertensive drugs including the thiazide-like diuretic chlorthalidone and the mineralocorticoid receptor antagonist spironolactone. “Pseudo resistance” especially due to white coat hypertension and non-adherence with the prescribed medication has to be ruled out to be able to identify patients with “true” treatment resistance. Therefore, before distinguishing true from pseudo resistance, the term “apparent” resistance should be used. While the prevalence of apparent resistance may be in the range of 10–15 % of treated patients, the exact prevalence of true resistance remains unknown due to the lack of appropriate studies but is likely to be rather small including a high proportion of patients with secondary forms of hypertension. Once identified most patients with true treatment resistance should receive intensified drug treatment primarily by expanded diuretic usage. Thus, resistant hypertension is primarily a diagnostic challenge: identifying patients with true resistance and those with secondary hypertension.
Keywords: Therapieresistenz; Pseudoresistenz; refraktäre Hypertonie; apparente Resistenz